The documentation archive as principal source for the study of independent theater during the Transition in Andalusia - Martín Martín, Francisco Marcos; Ruiz del Olmo, Francisco Javier; Merida Luque, Jesús (Revista General de Información y Documentación, 2016)
The independent theater had a great importance as an element of change during the political transition in Spain. However, it is an understudied socio-cultural movement. Of the shortcomings identified during the development of this research comes the main objective of this study: locate and describe the documentary that were created by the independent theater companies in Andalusia during the transition. To address this goal were consulted major national public archives; and Andalusia’s regional, provincial, municipal and university archives and specialized institutions. The results of this project will allow for an investigation on a virtually unexplored field of knowledge and with these nuances they provide written documentary sources. Also, with this work, we try to putthe importance of relevance posed to the knowledge of our history of preservation, systematization and dissemination of their cultural documentary heritage.